Diet and Lifestyle in the First Villages of the Middle Preceramic: Insights from Stable Isotope and Osteological Analyses of Human Remains from Paloma, Chilca I, La Yerba III, and Morro I. Issue 4 (December 2021) - Beresford-Jones, David G.; Pomeroy, Emma; Alday, Camila; Benfer, Robert; Quilter, Jeffrey; O'Connell, Tamsin C.; Lightfoot, Emma
Abstract : We present stable isotope and osteological data from human remains at Paloma, Chilca I, La Yerba III, and Morro I that offer new evidence for diet, lifestyle, and habitual mobility in the first villages that proliferated along the arid Pacific coast of South America (ca. 6000 cal BP). The data not only reaffirm the dietary primacy of marine protein for this period but also show evidence at Paloma of direct access interactions between the coast and highlands, as well as habitual mobility in some parts of society. By locating themselves at the confluence of diverse coastal and terrestrial habitats, the inhabitants of these early villages were able to broaden their use of resources through rounds of seasonal mobility, while simultaneously increasing residential sedentism. Yet they paid little substantial health penalty for their settled lifestyles, as reflected in their osteological markers of stature and stress, compared with their agriculturalist successors even up to five millennia later. Contrasting data for the north coast of Chile indicate locally contingent differences. Considering these data in a wider chronological context contributes to understanding how increasing sedentism and population density laid the foundations here for the emergence of Late Preceramic social complexity.